Development of a natural acid-base indicator from the bark extract of the red jambo (Syzygium malaccense L.) (REMUNOM, 2024)
The red jambo (Syzygium malaccense L.) is a tropical fruit known for its vibrant red color, which is due tothe presence of anthocyanins, a group of natural pigments. In this study, the extract obtained from the fruitpeel was used as a natural indicator. Experiments were conducted to evaluate its effectiveness as an acidbase indicator in different pH ranges. The results obtained revealed that the ketone extract demonstratedsuperior performance in the extraction of anthocyanins present in the samples, exhibiting distinct colorchanges in acidic and alkaline environments. Its ability to indicate pH variations through visual colorchanges makes it a practical and accessible choice for classroom demonstrations and laboratory research,contributing to a deeper understanding of fundamental chemistry concepts.